Direct and Efficient C(sp3)–H Functionalization of N-Acyl/Sulfonyl Tetrahydroisoquinolines (THIQs) With Electron-Rich Nucleophiles via 2,3-Dichloro-5,6-Dicyano-1,4-Benzoquinone (DDQ) Oxidation - Yu, Heesun; Kim, Hyoungsu; Baek, Seung-Hoon; Lee, Dongjoo (Frontiers in Chemistry, 2020)
A highly efficient metal-free oxidative direct C(sp3)–H functionalization of N-acyl/sulfonyl 1,2,3,4-tetrahydroisoquinolines (THIQs) with a wide range of electron-rich nucleophiles was accomplished under mild conditions through oxidation with DDQ and subsequent trapping of the resulting reactive and stable N-acyl/sulfonyl iminium ions. The synthetic utility of this method was illustrated by a concise and efficient total synthesis of (±)-benzo[a]quinolizidine (11) in 3 steps from the known N-Cbz-1,2,3,4-THIQ 4b.